PRESENCIA DE Xylophanes tersa (SPHINGIDAE: MACROGLOSSINAE) EN LA PROVINCIA DE LIMA (REBIOL, 2021)
* Autor para correspondencia: ragp1981@gmail.com                                   DOI: http://dx.doi.org/10.17268/rebiol.2021.41.02.12